Numerical simulation of stress relieving of an austenite stainless steel - Urevc, Janez (Strojniški vestnik, 2009)
An approach to numerical simulation of the annealing process with stress relieving is presented in the paper. For austenite stainless steel 316L (AISI), which exhibits no phase transformation from the melting point to room temperature, a viscous-elastic-plastic constitutive model is elaborated. First, from given experimental data the respective mechanical material parameters as a function of temperature are numerically identified by an inverse procedure. Then, the adequacy of the adopted model and identified material parameters is proven by a numerical simulation of stress relieving in two technological cases: (i) two-stage deep drawing with intermediate stress annealing and, (ii) simplified welding process followed by post weld heat treatment. In both cases the obtained residual stress state reduction is found to be in good agreement with the empirical experience and data provided from literature.
Keywords: žarjenje; avstenitno jeklo; mehanske lastnosti; modeliranje; simulacija